Development and initial psychometric evaluation of a radiotherapy‐related symptom assessment tool, based on data from patients with brain tumours undergoing proton beam therapy. Issue 3 (28th July 2020) - Langegård, Ulrica; Fransson, Per; Johansson, Birgitta; Ohlsson‐Nevo, Emma; Sjövall, Katarina; Ahlberg, Karin
Abstract : Background: Currently, no available tool easily and effectively measures both the frequency, intensity and distress of symptoms among patients receiving radiotherapy. A core symptom set (fatigue, insomnia, pain, appetite loss, cognitive problems, anxiety, nausea, depression, constipation, diarrhoea and skin reaction) has been identified and assessed across oncology research to better understand the pattern of symptoms and treatment side effects. Aim: The aim was to develop a tool measuring the multiple‐symptom experience in patients undergoing radiotherapy and evaluate its psychometric properties (validity, reliability and responsiveness). Design: This study has a prospective, longitudinal and quantitative design. Methods: We developed a patient‐reported outcome questionnaire, the Radiotherapy‐Related Symptoms Assessment Scale to assess the frequency, intensity and distress associated with symptoms. Patients (n = 175) with brain tumours undergoing proton beam therapy completed the Radiotherapy‐Related Symptoms Assessment Scale and the health‐related quality of life questionnaire (EORTC QLQ‐C30) during treatment. We assessed the validity, reliability and responsiveness of the Radiotherapy‐Related Symptoms Assessment Scale and evaluated the validity against QLQ‐C30. Results: There were significant questionnaire–questionnaire correlations regarding selected items, primarily fatigue, insomnia and pain, indicating satisfactory criterion‐related validity. The Radiotherapy‐Related Symptoms Assessment Scale had fair to good retest reliability. Conclusion: The Radiotherapy‐Related Symptoms Assessment Scale is a valid instrument for assessing symptom intensity and distress in patients with brain tumour undergoing PBT, with psychometric properties within the expected range. The Radiotherapy‐Related Symptoms Assessment Scale provides nurses with substantial information on symptom experience but requires little effort from the patient. Additional studies are required to further assess the psychometric properties in patients with different cancer diagnoses receiving conventional radiotherapy.